2020
DOI: 10.1016/j.apsb.2020.04.003
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of highly selective and orally available benzimidazole-based phosphodiesterase 10 inhibitors with improved solubility and pharmacokinetic properties for treatment of pulmonary arterial hypertension

Abstract: Optimization efforts were devoted to discover novel PDE10A inhibitors in order to improve solubility and pharmacokinetics properties for a long-term therapy against pulmonary arterial hypertension (PAH) starting from the previously synthesized inhibitor A . As a result, a potent and highly selective PDE10A inhibitor, 14· 3HCl (half maximal inhibitory concentration, IC 50 = 2.8 nmol/L and > 3500-fold selectivity) exhibit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 30 publications
0
19
0
Order By: Relevance
“…Paraffin-embedded tissues were sliced at a thickness of 5 μm and mounted on glass slides. Tissue sections were stained with hematoxylin and eosin (HE) as previously described . Pulmonary vascular remodeling was assessed by measuring the percent medial wall thickness of vessels (50–200 μm diameter).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Paraffin-embedded tissues were sliced at a thickness of 5 μm and mounted on glass slides. Tissue sections were stained with hematoxylin and eosin (HE) as previously described . Pulmonary vascular remodeling was assessed by measuring the percent medial wall thickness of vessels (50–200 μm diameter).…”
Section: Methodsmentioning
confidence: 99%
“…Tissue sections were stained with hematoxylin and eosin (HE) as previously described. 33 Pulmonary vascular remodeling was assessed by measuring the percent medial wall thickness of vessels (50−200 μm diameter). Vessel's external diameter and medial wall thickness (MT) were measured using a light microscope by an observer who was blinded to the treatment of rats.…”
Section: Methodsmentioning
confidence: 99%
“…In the meantime, the interfacing surface area between monomers also decreased ( Table S3 ), further weakening the intramolecular interactions and destabilizing dimerization. Moreover, by calculating the binding free energy between the ROC monomers with Molecular Mechanics/Poison Boltzmann Surface Area [ 49 , 50 , 51 ] (MM/PBSA), we further confirmed that ROCs, when bounded by GTP, were indeed less dimerized and therefore more prone to form the catalytically active monomers with hydrolysis activity than to be bound by its GDP counterparts.…”
Section: Resultsmentioning
confidence: 52%
“…The Δ G nonpolar was calculated using the function of the solvent accessible surface area (SASA) with the γ value of 0.0072 kcal/(mol Å 2 ) and the b value of 0 kcal/mol. The T Δ S was not computed in this work because of the extremely long durations of normal mode analysis for large systems ( Wang et al, 2019 ; Yang et al, 2020 ).…”
Section: Methodsmentioning
confidence: 99%